Simultaneous Larva Migrans and Larva Currens Caused by Strongyloides stercoralis: A Case Report - Liliam Dalla Corte; Mariana Vale Scribel da Silva; Paulo Ricardo Martins Souza (Hindawi Limited, 2013)
Strongyloidiasis is an infectious disease caused by the Strongyloides stercoralis larvae, which penetrate the skin, go through the lymphatic circulation, and migrate to the lungs before reaching the intestines. They mature and may cause cutaneous strongyloidiasis, known as larva currens because of the quick migratory rate of the larva. The authors describe a case in which the larvae did not follow their natural lymph route, and after penetrating into the intertriginous area, they migrated to the dermis, developing larva migrans in the early phase, and later associated with the typical lesions of larva currens. The diagnosis was confirmed by the presence of larva in the skin biopsy.